A Very Serious Thing : Women's Humor and American Culture - Walker, Nancy A., 1942- (Book collections on Project MUSE., 1988)
Defines why women have been blocked from participating in the mainstream of American comedy yet have overcome hurdles to produce a humor that is sustaining and spells survival for women in society.